Callus induction, plant regeneration and somaclonal variation in in vivo and in vitro grown White shrimp plant (Justicia betonica Linn.) - Yaacob, J.S.; Taha, R.M.; Jaafar, N.; Hasni, Z.; Elias, H.; Mohamed, N. (2013)
Justicia betonica Linn. is traditionally used to treat various illness like cough, scaly skin and as an erosion control plant. This paper reports on callus induction and in vitro propagation of J. betonica from 3-week-old petiole and internode explants of this species. Callus was readily induced from petiole explants when cultured on Murashige and Skoog's medium (MS) fortified with NAA (0.5-2.0 mg L-1), BAP (0.5-2.0 mg L-1), Kinetin (1.0-2.0 mg L-1) and Zeatin (1.0-2.0 mg L-1), while internode explants only showed formation of callus on MS basal and when 0.5 mg L-1 BAP or 1.5 mg L-1 Kinetin were added. Optimum in vitro regeneration in J. betonica had been successfully achieved using internode explants cultured on MS medium supplemented with 1.5 mg L-1 NAA and 0.5 mg L-1 BAP. Rhizogenesis was observed from petiole cultures supplemented with 1.0 mg L-1 NAA and 1.0 mg L-1 BAP as well as on MS with 1.5 mg L-1 NAA and 0.5 mg L-1 BAP, where the latter had shown the most optimum response, with percentage of root formation of 66.67 Â± 5.36. More hormone treatments were observed to yield rhizogenesis from internode explants, especially when cultures were fortified with 0.5 mg L-1 NAA and 1.0 mg L-1 BAP. Genetic stability in in vitro J. betonica plants was observed by studying the variation in mitotic index and chromosome numbers using cytological data. Similar values of mean Mitotic index (MI) and mean chromosome numbers (2n = 14) indicated that the transfer from in vivo to in vitro environment had no significant effect on genetic stability of this plant. However, the mean nuclear size was found to increase, while the mean cell size was reduced in in vitro J. betonica compared to in vivo plants. In vitro regenerated J. betonica plants were clonally uniform and showed no distinct morphological abnormalities, indicating the lack of somaclonal variation.